Adult acute epiglottitis - Arumainathan, Usha Devi; Siow, S. C.; Subha, Sethu Thakachy (Malaysian Medical Association, 2002)
Acute epiglottitis is a disease of rapid onset and progression of symptoms and has been well described in children. The importance of being aware of this diagnosis is to prevent an acute upper airway obstruction that can be potentially fatal. Here we describe two cases of adult acute epiglottitis where the patients had severe symptoms of sorethroat but a normal looking oropharynx.